Oliver and company [videorecording (Blu-Ray)] - Cox, Jim; Disney, Tim; Mangold, James; Redford, J. A. C.; Dickens, Charles, 1812-1870 (Disney Blu-ray., 2013)
In the heart of New York City, Oliver, a mischievous orphaned kitten, is befriended by Dodger, a carefree pooch, and his ragtag family of misfit mutts. Life gets even better for Oliver when he is adopted by a lonely little girl named Jenny. But when tough guy Sykes and his Doberman sidekicks try to keep Jenny and Oliver apart, the spirited kitten and his newfound friends discover the meaning of courage and find a home where they truly belong.